Tháng Hai 24, 2024

Cho biểu thức: \(M = (x – a)\left( {x – b} \right) + \left( {x – b} \right)\left( {x – c} \right) + \left( {x – c} \right)\left( {x – a} \right) + {x^2}\) Tính \(M\) theo \(a,b,c\) biết rằng \(x = \frac{1}{2}a + \frac{1}{2}b + \frac{1}{2}c\).

Cho biểu thức: \(M = (x – a)\left( {x – b} \right) + \left( {x – b} \right)\left( {x – c} \right) + \left( {x – c} \right)\left( {x – a} \right) + {x^2}\)

Tính \(M\) theo \(a,b,c\) biết rằng \(x = \frac{1}{2}a + \frac{1}{2}b + \frac{1}{2}c\).

A. \( a^2+b^2+c^2\)

B. \(a(b+c)+b(a+c)+c(a+b)\)

C. \(abc\)

D. \(ab+bc+ca\)

Hướng dẫn Chọn đáp án là: D

Lời giải chi tiết:

Hướng dẫn giải chi tiết

\(\begin{array}{l}\;\;\;\;\;M = \left( {x – a} \right)\left( {x – b} \right) + \left( {x – b} \right)\left( {x – c} \right) + \left( {x – c} \right)\left( {x – a} \right) + {x^2}\\ \Leftrightarrow M = x.x – b.x – a.x + a.b + x.x – c.x – b.x + b.c + x.x – a.x – c.x + a.c + {x^2}\\ \Leftrightarrow M = 4{x^2} – 2ax – 2bx – 2cx + ab + bc + ca\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\\ \Leftrightarrow M = 4{x^2} – 2x(a + b + c) + ab + bc + ca\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;(1)\end{array}\)

Theo đề bài ta có: \(x=\frac{1}{2}a+\frac{1}{2}b+\frac{1}{2}c\Leftrightarrow 2x=a+b+c\text{ }\left( 2 \right)\)

Thay (2) vào (1) ta được: \(M=4{{x}^{2}}-2x.2x+ab+bc+ca=ab+bc+ca\)

Chọn D.